Pengembangan LKPD Matematika Berbasis Problem Based Learning Untuk Meningkatkan Higher Order Thinking Skill Peserta Didik Sekolah Dasar - Seniawati Seniawati; Sri Supiyati; Marhamah Marhamah (Lembaga Bale Literasi, 2026)
The purpose of this study was to determine the practicality of developing a Mathematics Student Worksheet (LKPD) based on Problem-Based Learning (PBL) for fifth-grade students at Landah State Elementary School; to determine the validity of the Mathematics Student Worksheet based on Problem-Based Learning (PBL) for fifth-grade students at Landah State Elementary School; and to determine the effectiveness of the Mathematics Student Worksheet based on Problem-Based Learning (PBL) in improving higher-order thinking skills at fifth-grade students at Landah State Elementary School. The type of research used was Research and Development (RnD). The research model was ADDIE, an acronym for Analyze, Design, Develop, Implement, and Evaluate. Data collection techniques used were interviews and questionnaires. Data analysis techniques used were validity analysis, practicality analysis, and effectiveness analysis. The results of this study indicate that the practicality of the LKPD is demonstrated through the results of the teacher and student questionnaire responses, which obtained percentages of 97% and 95%, respectively, where these calculated percentages are considered very practical. The validity of the worksheet was demonstrated through assessments by learning experts, media experts, and language experts, which obtained a very good rating, and an Aiken's V index score that fell into the valid category. The effectiveness of the worksheet was evident in the significant improvement in student learning outcomes, with an average pretest score of 49.13 increasing to 80.43 on the posttest, with an N-Gain of 0.62, which falls into the moderate category.